Whiggery and Reform, 1830–41 - Newbold, Ian. author. aut Link
X, 401 p.
Keywords: This is a study of the parliamentary history of the Whigs during the Age of Reform, describing the extent to which both Grey and Melbourne's governments, with Peel's assistance, attempted to safeguard the interests of the landed aristocracy while allowing for moderate reforms in Church and State.